Green Craft Women: Pengembangan Produk Daur Ulang sebagai Wirausaha Sosial Perempuan Desa Sampali, Percut Sei Tuan Deliserdang - Harkim, Harkim; Sugiharto, Bambang; Simanungkalit, Rejekia V.; Andriani, Maya; De Hans, Nickytha Linch (Universitas Pahlawan Tuanku Tambusai, 2026)
Environmental issues from increasing non-organic waste, especially plastic and fabric scraps, have become serious in Sampali Village, Percut Sei Tuan District. Limited community knowledge, particularly among women, worsens the problem. To address this, the Green Craft Women program was developed as a community-based social entrepreneurship model empowering women to turn household waste into creative, eco-friendly crafts. The program integrates environmental preservation with economic empowerment through recycling training, small business management, digital marketing, and community branding. Implemented through observation, participatory training, and mentoring over three months, it involved 20 women from PKK and youth groups. Results showed improved waste management, entrepreneurial skills, and environmental awareness. Products such as recycled bags, wallets, and home decorations gained market appeal, supported by online promotion. This initiative fostered women’s independence, circular economy practices, and stronger community solidarity in environmental care.